Design and synthesis of protein arginine methyltransferase inhibitors - Hong, Wei (2010)
Biological methylation is defined as the transfer of a methyl group from S-adenosyl-L-methionine(SAM) to one of a wide range of potential acceptors such as DNA, RNA, protein, hormones and neurotransmitters. Protein arginine methylation is a common post-translational modification facilitated by protein arginine methyltransferases(e.g. PRMTI). The roles of these enzymes in vivo are currently poorly understood. The focus of the project is design and synthesis of PRMT inhibitors with the ultimate goal of evaluating their activities in cells. Preliminary work toward the synthesis of S-adenosyl-trifluoromethyl-L-homocystein and adenosyl 5'-[2-(tert-butoxycarbonylamino)ethyl-trifluoro methyl] thiophenium is described. The ternary crystal structure of PRMTI in complex with S-adenoSyl-L-homocystein(eSAH) and an arginine containing peptide (PBD IOR8) was used to design a series of potential bisubstrate inhibitors of PRMTI. The prototypical SAM analogues bearing guanidine group were sought to replace the reactive sulfonium centre with nitrogen. Analogue synthesis proceeded via successive reductive arnination of Y-arnino-Y-deoxyadenosine and deprotection in good overall yields. An alkyne SAM analogue, 5'-[(S-3-amino-3-carboxypropyl)-propargylaminol-5'-deoxyadenosine was prepared, which underwent efficient Cu(1) catalysed Huisgen reaction to yield a triazole derived SAM analogue 5'-[(S-3-amino-3-carboxypropyl)-[I-(2-guanidinoethyl)-IH-1,2,3-triazol-4-yl]methyl-amino]-5'-deoxyadenosine. Preliminary biological evaluation of the compounds by collaborators Professor Steve Ward and Dr Richard Parry at the University of Bath, confirmed that 5'-[(S-3-amino-3-carboxypropyl)- 3-guanidinopropyl-amino]-5'-deoxyadenosine and 5-[(S-3-amino-3-carboxypropyl)-5-guanidinopentyl-amino]-5'-deoxyadenosine are potent inhibitors of PRMTI but not the lysine methyltransferase SET7. A related N-6 modified SAM analogue 5'-[(S-3-amino-3-carboxypropyl)-3-guanidinopropylamino]-5'-deoxy-N6-(lI-azido-3,6,9-trioxaundecane)-amino adenosine bearing an azide tether was developed with the aim of allowing facile introduction of biotin or fluorescent dyes, using either Staudinger ligation, or Cu(1) catalysed Huisgen reaction to provide compounds that can be used for affinity purification of the target protein or study of its localisation in cells respectively. Finally, progress toward a novel, rapid and enantioselective synthesis of the natural product (+)-sinefungin is reported. Key dihydropyridazine intermediates were generated from adenosyl 5'-propaldehyde, commercially available azodicarboxylate derivatives and ester substituted vinyltriphenylphosphonium salt by successful extension of methodology first reported by Ley and co-workers. Deprotection and ring opening of clihydropyridazine compounds was attempted, and unfortunately we were not able to generate (+)-sinefungin, although it is hoped that this route can be developed to achieve this in the future.